ASSESSING THE INTEGRATION OF ARTIFICIAL INTELLIGENCE TOOLS IN FOREIGN LANGUAGE TEACHING DURING DISTANCE LEARNING: ASSESSING THE INTEGRATION OF ARTIFICIAL INTELLIGENCE TOOLS IN FOREIGN LANGUAGE TEACHING DURING DISTANCE LEARNING - Dilmanov, Ilya (Журнал иностранных языков и лингвистики, 2025)
The integration of technology in education has been a growing trend over the past few decades. In this context, AI tools have gained prominence due to their potential to personalize learning, provide immediate feedback, and enhance student engagement (Hwang et al., 2020). This paper assesses the impact of these tools on foreign language teaching, focusing on their effectiveness, benefits, and challenges.